Biocompatibility of an adhesive system and 2-hydroxyethylmethacrylate - Costa, CAD; Teixeira, H. M.; do Nascimento, ABL; Hebling, J. (Amer Soc Dentistry Child, 1999)
The aim of the study was to evaluate the biocompatibility of an adhesive system and a resin component when implanted into connective tissue of rats. Forty sponges embedded in both materials: Scotchbond MP (SBMP/3M - Group A) and 2 - hydroxyethyl-methacrylate (HEMA - Group B), were implanted into dorsal connective tissue of 20 animals. After 7, 15, 30, or 60 days of the implantation, the animals were sacrificed; implant sites were excised and immersed for 24 hours in Kamovisky's fixative. The samples were processed under routine histologic technique, being stained with H & E. Histological evaluation showed that both materials promoted at 7 days intense inflammatory response with predominance of neutrophils and macrophages. The intense connective reaction was replaced for fibroblastic proliferation associated with macrophages and foreign body giant cells over time. The persistent moderate inflammatory reaction adjacent to scattered fragments of materials was greater to HEMA than to the SBMP. Both experimental materials did not show acceptable biocompatibility with connective tissue of rats in spite of allowing an evident connective tissue healing.